Behavioural response of pure Ankole and crossbred(Ankole × Holstein) cows to seasonal pasturevariations in south-western Uganda - Idibu, Joachine; Kabi, Fred; Mpairwe, Denis (Applied Animal Behaviour Science, 2016)
tThis study evaluated the effects of season and pasture species on variations in sward composition, pasture quantity (plant-height and biomass) and quality [crude protein (CP), neutral detergent fibre (NDF)and in vitro organic matter digestibility (IVOMD)]. Behavioural responses of a group of 10 pure Ankole and another of 10 crossbred (Ankole × Holstein) cows to the seasonal variations in pasture quantity and quality were also examined. Irrespective of season, the dominant pasture species was Brachiaria decum-bens, with scanty presence of Hyparrhenia rufa, Themeda triandra, Sporobolus pyramidalis and Cymbopogonafronardus. The sward height, biomass, CP, NDF and IVOMD were dependent on both season and species(P < 0.001). Whereas the sward-height and biomass of B. decumbens, H. rufa, and T. triandra peaked during the rainy season, that of C. afronardus and S. pyramidalis peaked in the dry season. During the grazing cycle, a minimum plant-height of 31 cm and forage biomass of 118 g/m2, an equivalent of 1180 kg/ha,was recorded for most of the pasture species. The CP content of the pasture species were below 7%,irrespective of season, except for B. decumbens which had 8.7% CP in the rainy season. Minimum NDFcontent for all the pasture species was 67% and 50% during the dry and rainy seasons, respectively. Con-sequently, IVOMD ranged between 29–61% and 51–65% during the dry and rainy seasons, respectively. Ankole and the crossbred cows increased the number of feeding stations, bites and residence time in patches of species, which were scantly grazed in the rainy season. They also increased standing (P < 0.01)at the expense of walking (P < 0.001) and social activities (P < 0.001). Irrespective of season, more than40% of grazing occurred in B. decumbens patches and both genotypes grazed for ¾ of the time on pasture.However, the crossbred cows required extended grazing duration, resulting into less lying and rumi-nation (P < 0.05) on pasture than the Ankole cows. Ankole and the crossbred cows grazed locales with high pasture ground cover and biomass. However, locales with high CP but low forage quantity were also grazed. This study revealed that at an appropriate stocking rate, sufficient forage supply was possible in both seasons. However, the low CP content and less preference for majority of the dominant species compelled the Ankole and the crossbred cows to graze for a long time. Thus, the crossbred cows were constrained by time in both the dry and rainy seasons.
Keywords: Ankole cattle; Crossbred cows; Grazing behaviour; Pasture species; Season